1991
DOI: 10.1203/00006450-199108000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lung Distension, Oxygenation, and Gestational Age on Fetal Behavior and Breathing Movements in Sheep

Abstract: ABSTRACT. Lung distension with 100% 0 2 at a continuous positive airway pressure of 30 cm H 2 0 may induce continuous fetal breathing movements (FBM) in sheep. The objectives of this study were 1 ) to investigate the relative roles of lung distension and oxygenation and 2) to test the hypothesis that FBM can be induced during labor, when normally they are greatly reduced or absent. We studied 13 chronically instrumented, unanesthetized fetal sheep between 128 and 144 d of gestation (term = 147 f 2 d). Each fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Twin lambs were delivered electively by Cesarean section at 126 days gestation (term ϭ 147 Ϯ 2 days) (Hasan and Rigaux, 1991). The ewe was mated on a specific day to allow precise knowledge of gestational age.…”
Section: Materials and Methods Delivery And Management Of The Lambsmentioning
confidence: 99%
“…Twin lambs were delivered electively by Cesarean section at 126 days gestation (term ϭ 147 Ϯ 2 days) (Hasan and Rigaux, 1991). The ewe was mated on a specific day to allow precise knowledge of gestational age.…”
Section: Materials and Methods Delivery And Management Of The Lambsmentioning
confidence: 99%
“…We had ventilated fetuses with oscillating positive Recent studies have demonstrated that spontaneous negative pressures; the possibility that high intrathoracic pressures pressure pulmonary ventilation can be initiated and maintained adversely affected cardiac output could not be ruled out. in fetal sheep when the umbilical cord is occluded while oxygen To determine the effects of negative intrathoracic pressure is introduced into the fetal trachea (7)(8)(9)(10). We applied this ventilation, we occluded the umbilical cord of nine long-technique to determine the effects of spontaneous, rhythmic term instrumented fetal sheep at 135 f 1.2 d gestation pulmonary ventilation on blood flow patterns at birth.…”
mentioning
confidence: 99%
“…Breathing stopped at a Pao2 of 38.5 +: 9.5 torr (5.1 f 1.3 kPa) but could be restarted by increasing the Pao2. In response to an increase in fetal Pao, (4)(5)(6)(7)(8), amplitude of breathing and total respiratory output significantly increased from the control values. Further increases in Pao2 or Hb O2 saturation did not significantly affect the respiratory output.…”
mentioning
confidence: 97%
“…In sheep, during late gestation, FBM occupy 40% of the total time and normally occur only during LV-ECoG but are absent during HV-ECoG (3). Recent studies have shown that an increase in fetal Pao2 achieved by distending the fetal lungs with 100% O2 at a CPAP of 30 cm H 2 0 may stimulate FBM during both LV-and HV-ECoG (4,5). In our previous study (5) initiation of breathing was always associated with the onset of fetal arousal and was critically dependent on fetal maturity.…”
mentioning
confidence: 99%
See 1 more Smart Citation